‘New’ Radio Policies for Non-commercial Media in Mexico - Rueda de León Contreras, Luz de Azucena; Mota, Laura (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2014)
Public policies in Mexico have privileged the commercial aspect of radios over the social function of non-profit media. Despite the recent constitutional reforms that were announced as the beginning of new policies designed to satisfy the most diverse needs of communication and information, the demands of civil society to consolidate an atmosphere of media plurality have not been attended to. This article centers on the reasons for which the aspirations of civil society in this area have not materialized. With this objective, we focus on the evident disunity that has characterized communication public policies in Mexico with respect to two elements that are part of radio as a cultural industry – its economic aspect and its socio-cultural aspect.